A GOP-level fuzzy rate control algorithm for high-delay applications of HEVC. Issue 7 (October 2016) - Fani, Davoud; Rezaei, Mehdi
Abstract The high -efficiency video coding (HEVC) standard was introduced for high-resolution video contents suitable for many high-delay applications. The bit rate of compressed video is controlled in almost all digital video applications according to the practical constraints such as available channel bandwidth and allowed delay or buffering constraint. In high-delay video applications such as video broadcasting and video streaming applications, variable-bit-rate videos can provide a higher visual quality than constant-bit-rate videos. In this paper, a rate control algorithm (RCA) for high-delay applications of the HEVC standard with buffering constraint is proposed. A fuzzy controller and a virtual buffer are used in the proposed RCA. The fuzzy controller is designed to minimize the fluctuations of quantization parameter (QP) while the buffering constraint is obeyed. It computes a base QP for each group of pictures (GOP) to prevent unnecessary fluctuations of QP at GOP level and thereafter provide a higher visual quality. Experimental results show that not only the bit rate and but also buffering constraints are fully maintained but also the objective quality of compressed video is well preserved. Moreover, the proposed RCA provides smooth QP and peak signal-to-noise ratio close to constant QP case for encoded videos that means high subjective quality.